2014
DOI: 10.1016/j.tins.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Drowning stars: reassessing the role of astrocytes in brain edema

Abstract: Edema formation frequently complicates brain infarction, tumors and trauma. Despite the significant mortality of this condition, current treatment options are often ineffective or incompletely understood. Recent studies have revealed the existence of a brain-wide paravascular pathway for cerebrospinal (CSF) and interstitial fluid (ISF) exchange. The current review critically examines the contribution of this ‘glymphatic’ system to the main types of brain edema. We propose that in cytotoxic edema, energy deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
162
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 110 publications
0
162
0
3
Order By: Relevance
“…Alternatively CAA may disrupt perivascular drainage via perturbations in normal arteriolar pulsation (Hawkes et al, 2014;Kress et al, 2014). It is also possible that the presence of hyper-phosphorylated tau has direct deleterious consequences for perivascular astrocytes, for example by directly disrupting their microtubular structure, or altering the expression or localisation of membrane channels (for example, aquaporin 4) that change normal interstitial fluid dynamics, with the eventual outcome of an enlarged perivascular space (Arima et al, 1998;Thrane et al, 2014;Iqbal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively CAA may disrupt perivascular drainage via perturbations in normal arteriolar pulsation (Hawkes et al, 2014;Kress et al, 2014). It is also possible that the presence of hyper-phosphorylated tau has direct deleterious consequences for perivascular astrocytes, for example by directly disrupting their microtubular structure, or altering the expression or localisation of membrane channels (for example, aquaporin 4) that change normal interstitial fluid dynamics, with the eventual outcome of an enlarged perivascular space (Arima et al, 1998;Thrane et al, 2014;Iqbal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…4 However, the cardiac pulsation provides no more than 15-25% of the propulsive energy and other pulsation mechanisms must contribute to the convective CSF fluid dynamics. 6 Early functional magnetic resonance imaging (fMRI) scans and other modalities have shown that there may be several sources of pulsations in the brain. [7][8][9][10][11] The spectrum of susceptibilityweighted blood oxygen level dependent (BOLD) signals shows a 1/f frequency profile with most pulsatile power in very low frequencies ( < 0.1 Hz) and distinct respiratory rate (0.2-0.3 Hz) and cardiac frequency (0.8-1.2 Hz) peaks.…”
Section: Introductionmentioning
confidence: 99%
“…11,12) During TBI, cerebral ischemia, or hemorrhage, all of which cause BBB disruption, vasogenic edema is commonly observed and persists for several days after brain damage. 12,13) Severe damage to endothelial cells and a decrease of endothelial tight junction proteins results in BBB disruption leading to vasogenic edema. 11) In common with many types of brain damage, several physiological active substances including vascular endothelial growth factors (VEGFs) and matrix metalloproteinases (MMPs) are responsible for vasogenic edema formation through tight junction dysfunction.…”
Section: Brain Edemamentioning
confidence: 99%
“…3,13) Cerebral hemorrhage is a lethal condition, which results in sudden death, paralysis of the extremities, and cognitive dysfunctions. Hemorrhage results from a fracture of microvessels by cerebral contusions.…”
Section: Hemorrhagementioning
confidence: 99%